Chitosan-based Scaffolds, Suitable Structures for Wound Healing Dressing: A Short Review - Taghipour, Niloofar; Deravi, Niloofar; Rahimi, Mohsen (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Different kinds of substances has been used for wound dressing, however, some disadvantages such as unsatisfactory mechanical stability, poor flexibility, severe shrinkage, low porosity, hard separation from the wound site, and non-antibacterial activity, has been reported. Over the last two decades, much effort has been made to find suitable biopolymer materials for wound healing applications. Chitosan has revealed various biological properties like biodegradable, biocompatible, non-toxic and non-allergenic, antibacterial effects thus can be used for the production of biofilms and nano-scaffolds. The poor solubility and thermal properties of chitosan restrict its widespread uses, but this polysaccharide is highly compatible with other biopolymers, and researchers are using this property to improve the limitations of chitosan and produce various types of chitosan-based hybrids materials. The purpose of this study is to provide an overview of various chitosan-based nanoscaffolds as wound healing dressings. Materials and Methods: This narrative review was performed using ISI Web of Science, PubMed, SID, Scholar, Scopus, and Science Direct and articles published up to Jan 2020 were included. The keywords of chitosan, chitosan-based scaffolds, chitosan-based composite, and wound dressing were used. Results: Many researches have been accomplished to obtain chitosan-based scaffolds, including the construction of chitosan based blends and composite scaffolds and etc. The results of most of these researches showed positive effects of chitosan, and its nanocomposite scaffolds/biofilms in blood clotting, activated platelet activity, facilitated tissue regeneration and wound healing process. Conclusion: The use of chitosan-based scaffolds is effective in biological dressings and wound healing. Futuristic and innovative approaches in chitosan derivatives and nanocomposites can lead to the preparation of suitable co-polymers and the production of wound dressings with the desired properties. the authors hope that this review will help for researchers.